2015
DOI: 10.1038/srep12500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RNA silencing components in the plant pathogenic fungus Fusarium graminearum

Abstract: The RNA interference (RNAi) plays a critical role in gene regulation in a variety of eukaryotic organisms. However, the role of RNAi remains largely unclear in plant pathogenic fungi. In this study, we explored the roles of core components of the RNAi pathway in Fusarium graminearum, the major causal agent of wheat head blight. Our results demonstrated that the hairpin RNA (hpRNA) can efficiently silence the expression level of target gene, and the argonaute protein FgAgo1 and dicer protein FgDicer2 are import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
126
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(149 citation statements)
references
References 64 publications
9
126
0
Order By: Relevance
“…In fungi, several classes of sRNAs, including miRNA-like RNAs, Dicer-independent siRNAs (Lee et al, 2010), qiRNA, esRNA (Lee H.C. et al, 2009; Nicolas et al, 2010; Nunes et al, 2011b; Chen et al, 2015), and tsRNAs (Jochl et al, 2008; Thompson et al, 2008; Thompson and Parker, 2009; Nunes et al, 2011a) have been identified. However, no canonical miRNAs have been reported (Nunes et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…In fungi, several classes of sRNAs, including miRNA-like RNAs, Dicer-independent siRNAs (Lee et al, 2010), qiRNA, esRNA (Lee H.C. et al, 2009; Nicolas et al, 2010; Nunes et al, 2011b; Chen et al, 2015), and tsRNAs (Jochl et al, 2008; Thompson et al, 2008; Thompson and Parker, 2009; Nunes et al, 2011a) have been identified. However, no canonical miRNAs have been reported (Nunes et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Possible transfer routes for both mechanisms via vesicles or RNA-transporters are indicated. AGO1 seems to be essential for the RNAi response in Fusarium (Chen et al 2015) FgCYP51B is most important for ergosterol biosynthesis and thus survival of the fungus (Fan et al 2013;Liu et al 2011;Machado et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several sRNAs show differential expression in the Δdcl2 mutant and WT, which suggests that the sRNAs generated by Mrdcl2 may be associated with the regulation of conidiation in M. robertsii (see Table S6 in the supplemental material). In particular, milRNAs, including those in N. crassa (40), Penicillium marneffei (43), Sclerotinia sclerotiorum (44), and Fusarium graminearum (45), have been identified, and they have an important function in regulating different biological processes in these fungi. Previously, it was discovered by our group that milRNAs may play an important role in the regulation of conidiation in M. robertsii (24).…”
Section: Discussionmentioning
confidence: 99%